Ε-Polylysine-based thermo-responsive adsorbents for immunoglobulin adsorption–desorption under mild conditions. (20th June 2017) - Maruyama, Masashi; Shibuya, Keisuke
Abstract : Thermo-responsive adsorbents for immunoglobulin G (IgG) employing ε-polylysine (EPL) as a polymer backbone were developed. Abstract : Thermo-responsive adsorbents for immunoglobulin G (IgG) employing ε-polylysine (EPL) as a polymer backbone were developed. The introduction of mercaptoethylpyridine (MEP) as an IgG-binding ligand and hydrophobization of side chains afforded thermo-responsive IgG adsorbents, whose thermo-responsive IgG desorption ratio was up to 88% (EPL/MEP derivative3m ). The changes in surface densities of active MEP groups, which are caused by thermal conformational changes of the adsorbents, play key roles for IgG desorption. Although a trade-off of IgG adsorption capacity and IgG desorption ratio was observed, the present study offers a novel molecular design for thermo-responsive adsorbents with high synthetic accessibility and potentially low toxicity.